Mesoscale Models From Micro-Physics to Macro-Interpretation - Mesarovic, Sinisa; Forest, Samuel; Zbib, Hussein (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2019)
The book helps to answer the following questions: How far have the understanding and mesoscale modeling advanced in recent decades, what are the key open questions that require further research and what are the mathematical and physical requirements for a mesoscale model intended to provide either insight or a predictive engineering tool? It is addressed to young researchers including doctoral students, postdocs and early career faculty.